Anthropomorphism and Zoomorphism in the Ornamental Art of the Crimean Tatars - Akchurina-Muftieva N.M. (Золотоордынское обозрение)
The author of the article reveals the problem of anthropomorphic and zoomorphic images in Islamic art, particularly in the Turkic ornamentation of the Crimea. Superficial, unscientific interpretations of motifs and ornamental compositions often lead to the search for and appropriation of anthropomorphism without appropriate research, loose interpretations of motifs, and the creation of a new mythology. Despite conservative views regarding the categorical denial of the permissiveness of the image of a person, there are many surviving works of fine and decorative art that confirm an opposite tradition. Currently, there are practically no studies of anthropomorphism and zoomorphism in the Turkic ornamentation of the Crimea, their typological and artistic features, and their symbolic context. Based on the material of decorative and applied art of the Crimean Tatars from the fourteenth century to the present, examples of zoomorphic and anthropomorphic ornamental images are provided in the article. They are stylized objects – fully, partially, or in the form of a silhouette – reflecting the surrounding real world of living beings. Complete naturalistic images (birds, fish, animals, insects) are found on objects until the first half of fifteenth century, and then starting again from the second half of eighteenth century. From the sixteenth to the first half of eighteenth centuries, anthropomorphic and zoomorphic motifs were depicted in a stylized form. The author of the study reveals the symbolism of the most common motifs, along with the typological and artistic features of the images. As a result of the study, it was revealed that the color, silhouette, and figurativeness of anthropomorphic and zoomorphic images in the Crimean Tatar decorative and applied art depend primarily on the material, technique, and functional purpose of the created object. In addition to images on objects, anthropomorphism is present as the silhouette of objects.